2014
DOI: 10.1016/j.coph.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Ca2+ in gastric epithelial restitution—new views revealed by real-time in vivo measurements

Abstract: It has been a few decades since Ca2+ was identified as one of the important factors that can accelerate gastric wound repair as well as contribute to epithelial homeostasis and regulation of gastric secretions. The mechanistic basis has remained largely unexplored in vivo because it was not possible to track in real time either intracellular Ca2+ mobilization or wound repair in living tissues. Recent advances in technology, such as combining high resolution light microscopy and genetically encoded Ca2+ reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…; Aihara et al . ; Aihara & Montrose, ). We have recently demonstrated that the gastric organoid system is comparable to native tissue in vivo with respect to demonstrating the shedding of dead cells into the gastric lumen with an epithelial repair time course of ∼10 min (Aihara et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Aihara et al . ; Aihara & Montrose, ). We have recently demonstrated that the gastric organoid system is comparable to native tissue in vivo with respect to demonstrating the shedding of dead cells into the gastric lumen with an epithelial repair time course of ∼10 min (Aihara et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our work points to the critical role of voltage‐gated and SOCE Ca 2+ channels (extracellular) and PLC, IP 3 (intracellular) pathways to promoting repair. We have previously shown in vivo the importance of localized changes in both extracellular and intracellular Ca 2+ during gastric epithelial repair (Aihara et al, 2013; Aihara & Montrose, 2014) in the first study to demonstrate Ca 2+ dynamics occurring in native tissue during gastric restitution with a genetically encoded Ca 2+ indicator. Due to tissue motion in a breathing animal, it is technically challenging to examine Ca 2+ dynamics in individual cells during the response to single cell damage (unpublished observations) .…”
Section: Discussionmentioning
confidence: 99%
“…Early epithelial restitution is a primary repair modality in the gastrointestinal tract, and it rapidly reseals superficial wounds by migrating visible remaining epithelial cells from areas adjacent to the injured surface to cover the wounded area, followed by proliferation and differentiation (4,5). This early rapid mucosal reepithelialization after mucosal injury is a complex process that includes the flattening, spreading, migrating, and repolarizing of differentiated columnar epithelial cells but is independent of cell proliferation (2,6). Defective regulation of early mucosal restitution underlies various critical pathological states such as massive mucosal injury and hemorrhage, delayed wound healing, disruption of epithelial integrity, and epithelial barrier dysfunction (2, 7).…”
mentioning
confidence: 99%